THE RELATIONSHIP OF MULTIPLE ROLE CONFLICT AND JOB STRESS THROUGH WORK MOTIVATION AS AN INTERVENING VARIABLE ON PERFORMANCE IN FEMALE EMPLOYEES AT MITRA MEDIKA BANDAR KLIPPA HOSPITAL - Muhammad Zikri Atthariq Daulay; Nazaruddin; Iskandarini (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Based on the results of research and discussions that have been carried out previously, it can be concluded as follows: Multiple Role Conflict has a positive and significant effect on Work Motivationon Female Employees at Mitra Medika Bandar Klippa Hospital. Multiple Role Conflict has a positive and significant effect on Performanceon Female Employees at Mitra Medika Bandar Klippa Hospital. Job Stress has a positive and significant effect on Work Motivationon Female Employees at Mitra Medika Bandar Klippa Hospital. Job Stress has a positive and significant effect on Performanceon Female Employees at Mitra Medika Bandar Klippa Hospital. Work Motivation has a positive and significant effect on Performanceon Female Employees at Mitra Medika Bandar Klippa Hospital. Multiple Role Conflict has a positive and significant effect on Performance through Work Motivationon Female Employees at Mitra Medika Bandar Klippa Hospital. Job Stress has a positive and significant effect on Performance through Work Motivationon Female Employees at Mitra Medika Bandar Klippa Hospital.